Schisandrin B Antagonizes Cardiotoxicity Induced by Pirarubicin by Inhibiting Mitochondrial Permeability Transition Pore (mPTP) Opening and Decreasing Cardiomyocyte Apoptosis - Shi, Hongwei; Tang, Heng; Ai, Wen; Zeng, Qingfu; Yang, Hong; Zhu, Fengqing; Wei, Yunjie; Feng, Rui; Wen, Li; Pu, Peng; He, Quan (Frontiers in Pharmacology, 2021)
Objective: Pirarubicin (THP), one of the anthracycline anticancer drugs, is widely used in the treatment of various cancers, but its cardiotoxicity can not be ignored. Schisandrin B(SchB) has the ability to up regulate cellular antioxidant defense mechanism, promote mitochondrial function and antioxidant status. However, it has not been reported whether it can resist THP induced cardiotoxicity. The aim of this study was to investigate the effect of SchB on THP cardiotoxicity and its mechanism. Methods: The rat model of cardiotoxicity induced by THP was established and SchB treatment was performed at the same time. The changes of ECG, cardiac coefficient, and echocardiogram were observed. The changes of myocardial tissue morphology were observed by HE staining. Apoptosis was detected by TUNEL. The levels of LDH, BNP, CK-MB, cTn-T, SOD and MDA were detected. The expression of Cleaved-caspase 9, Pro/Cleaved-caspase 3, Bcl-2/Bax and cytosol and mitochondrial Cyt C were evaluated by Western blot. H9C2 cardiomyocytes were co cultured with THP, SchB and mPTP inhibitor CsA to confirm these signaling pathways. The opening of mPTP in cardiomyocytes was detected by mPTP assay kit. Results: After 8 weeks, a series of cardiotoxicity manifestations were observed in THP rats. These adverse effects can be effectively alleviated by SchB treatment. Further studies showed that SchB had strong anti-apoptotic ability in THP induced cardiotoxicity. Conclusion: SchB has an obvious protective effect on THP-induced cardiotoxicity. The mechanism may be closely related to its inhibition of mPTP opening and the alleviation of cardiomyocyte apoptosis.